Preparation of Additional Monoclonal-Antibodies for Detection and Discrimination of Potato Virus-Y Isolates Infecting Potato - Sanz, Antonio; Cambra, Mariano; Desanroman, C. P.; Miguet, J. G.; Cortes, E.; Gorris, María T.; Vela, C. (2017)
Monoclonal antibodies (MAb) specific to potato virus Y (PVY) were obtained from hybrid cells produced by fusion of a non-secreting myeloma cell line with spleen cells from BALB/c mice immunized with isolate Bintje PVY(o). Six MAb were characterized. The reactions of the Mab have been assayed by indirect double-antibody sandwich enzyme-linked immunosorbent assay (ELISA-IDAS) against forty-nine PVY isolates and other potyviruses, representative of different potato areas in the world. All MAb reacted to at least some isolates in group O + C in ELISA-IDAS. One MAb did not react to any group N isolates. MAb 10E3 reacted to all isolates tested. Using standard double-antibody sandwich enzyme-linked immunosorbent assay (ELISA-DAS), two MAbs did not react to any isolates, one reacted to some isolates in group O + C and MAb 10E3 reacted to all isolates but two in group C. A mixture of MAb 10E3 and 1E10 detected all isolates in ELISA-DAS and sensitivity was improved over that obtained with polyclonal antibodies from antisera.